Final safety and efficacy analysis of a phase I/II trial with imatinib and vinorelbine for patients with metastatic breast cancer - Maass, Nicolai; Schem, Christian; Bauerschlag, Dirk O.; Tiemann, Katharina; Schaefer, Fritz W.; Hanson, Sven; Muth, Mathias; Baier, Monika; Weigel, Marion T.; Wenners, Antonia S.; Alkatout, Ibrahim; Bauer, Maret; et al. (Oncology, 2014)
Background: Imatinib is a tyrosine kinase inhibitor of BCR-ABL, ABL, PDGFR-α and -β, KIT, and DDR. In solid tumors, it inhibits proliferation and invasiveness and facilitates higher intratumoral cytotoxic drug concentrations. Vinorelbine has good tolerability and efficacy in metastatic breast cancer (MBC). This study evaluates the safety and efficacy of imatinib and vinorelbine in combination.
CRIS-Team Scopus Importer:2022-11-17
Keywords: Imatinib mesylate; KIT; Metastatic breast cancer; PDGFR-α and -β; Phase I/II trial; Vinorelbine